Reproductive History in Takotsubo Syndrome, A Register-Based Cohort Study - Tornvall, Per; Pettersson, Hans Järnbert (Frontiers in Cardiovascular Medicine, 2021)
Background: Takotsubo syndrome (TS) is a recently recognized serious heart condition that mainly affects women. Despite that 80–90% of the patients are women, few studies have focused on sex-specific characteristics such as female sex hormones and reproductive history. The aim of the study was to compare reproductive history in patients with TS with controls. Methods: This register-based cohort study compared reproductive history and off-spring birth characteristics between 158 TS patients without coronary artery stenoses and 236 age- and sex-matched controls (C) with coronary artery stenoses because of acute coronary syndrome (ACS-C), respectively, 285 without coronary artery stenoses with chest pain (CP-C). Results: There were no differences in pregnancy complications between TS and CP-C. Gestational length did not differ, but infants born to TS patients had lower birth weight for gestational age than CP-C with an odds ratio of 1.7 (95% confidence interval 1.2–2.5) for infants born small. Conclusion: The results showing an association between birth weight for gestational age and TS later in life are hypothesis-generating. The association is not likely causal and before delivery of small for gestational age infants can be considered as a risk marker for TS later in life the results need to be confirmed in independent studies